1998
DOI: 10.1080/10587259808042429
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Phase Transition Behavior of Polymer Azobenzene Liquid Crystals with a Rigid Core Introduced at a Different Position in a Flexible Side Chain

Abstract: Photochemical phase transition behavior of polymer azobenzene liquid crystals (LCs) was explored by transmission-mode analysis and reflection-mode analysis. Four samples with different structures were used, which show LC behavior in the trans form but no LC phase in the cis isomer. Attention was focused on the effect of the position of the mesogenic azobenzene moiety in the flexible side chain on the photochemical phase transition behavior. Photoirradiation of a thin film of the azobenzene LCs (-200 nm) in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…To overcome this difficulty, a new system has been developed, in which every mesogen in LCs or PLCs is provided with a photosensitive moiety. [87][88][89][90][91][92][93][94][95][96][97] It has been found that some azobenzene derivatives exhibit LC behavior. In these azobenzene LCs, the azobenzene moiety could play both roles as a mesogen and as a photosensitive moiety (Fig.…”
Section: -2 Photochemical Phase Transition Of Polymer Azobenzene Lcsmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this difficulty, a new system has been developed, in which every mesogen in LCs or PLCs is provided with a photosensitive moiety. [87][88][89][90][91][92][93][94][95][96][97] It has been found that some azobenzene derivatives exhibit LC behavior. In these azobenzene LCs, the azobenzene moiety could play both roles as a mesogen and as a photosensitive moiety (Fig.…”
Section: -2 Photochemical Phase Transition Of Polymer Azobenzene Lcsmentioning
confidence: 99%
“…90 The effect of the spacer between the polymer main chain and the azobenzene chromophore on the photochemical phase transition behavior was explored in detail. [91][92][93] Fig. 15 Examples of azobenzene LCs.…”
Section: -2 Photochemical Phase Transition Of Polymer Azobenzene Lcsmentioning
confidence: 99%
“…LC poly-(meth)acrylates with azobenzene photochromic side chains. 11,[25][26][27][28] On the other hand, we have reported similar mesophases for numerous chiral homopolymers (polymethacrylates, polysiloxanes) [29][30][31][32] and their copolymers with nonchiral azodye comonomers. 24,33,34 The detailed study of the "transparent smectic mesophase" is presented in our recent paper; 32 here we will summarize them briefly.…”
Section: Resultsmentioning
confidence: 84%
“…32 To overcome this issue, next to the addition of plasticizers, 31 flexible polydimethylsiloxane chains have been used to improve the segmental mobility of the main chain and facilitate the molecular reorientation of the chromophores by light. [33][34][35][36][37] However, for these materials, the nanoscale organization is limited due to the polydispersity of the polydimethylsiloxane chains, which limits the cooperative motion of the photo-switches. Despite these promising results, design strategies to form flexible photo-responsive materials with highly ordered nanostructures are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the photo‐responsiveness of polymers containing azobenzene as part of the main chain is typically inefficient, particularly in thin film due to the restricted motion of the rigid polymer chains 32 . To overcome this issue, next to the addition of plasticizers, 31 flexible polydimethylsiloxane chains have been used to improve the segmental mobility of the main chain and facilitate the molecular reorientation of the chromophores by light 33–37 . However, for these materials, the nanoscale organization is limited due to the polydispersity of the polydimethylsiloxane chains, which limits the cooperative motion of the photo‐switches.…”
Section: Introductionmentioning
confidence: 99%